2001
DOI: 10.1111/j.1553-2712.2001.tb00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patient Visits to an Urgent Care Clinic Using Calendar Variables

Abstract: Abstract. Objective: To develop a prediction equation for the number of patients seeking urgent care. Methods: In the first phase, daily patient volume from February 1998 to January 1999 was matched with calendar and weather variables, and stepwise linear regression analysis was performed. This model was used to match staffing to patient volume. The effects were measured through patient complaint and ''left without being seen'' rates. The second phase was undertaken to develop a model to account for the contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 15 publications
(21 reference statements)
5
88
1
Order By: Relevance
“…Earlier studies [3][4][5][6][7] suggested that some patients delay seeking treatment until after the holidays. These studies did not investigate whether such delays produced additional deaths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies [3][4][5][6][7] suggested that some patients delay seeking treatment until after the holidays. These studies did not investigate whether such delays produced additional deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [3][4][5][6][7] show that admissions to urgent care facilities drop on holidays and spike immediately thereafter. This phenomenon may occur because some patients inappropriately delay seeking medical services to avoid disrupting their holidays.…”
Section: Possible Explanations For the Cardiac Holiday Peakmentioning
confidence: 97%
See 1 more Smart Citation
“…We made all our models sensitive to the hour of the day and the day of the week because previous studies have found that ED arrivals vary significantly across these two calendar variables [2 -7]. In addition, we included the month of the year in one of our models because several studies have found that ED arrivals also vary with this calendar variable [7,8,11,12]. Our main interest was to forecast hourly arrivals and hourly occupancy but to assess the effect of the length of the forecasting interval on the accuracy of the models we made models for intervals of 1, 2, 4, 8, and 24 hours.…”
Section: Modelsmentioning
confidence: 99%
“…Previous approaches to the winter surge in emergency demand in adult intensive care have involved using disease surveillance (Hiller et al, 2013;Moriña et al, 2011;Nguyen et al, 2016), and/or weather and seasonal information (Batal et al, 2001;Boyle et al, 2012;Diehl et al, 1981;Jones et al, 2002;Marcilio et al, 2013;Shiue et al, 2016), and/or previous demand (Abraham et al, 2009;Jones, 2007;Jones et al, 2008;Proudlove et al, 2003), using a range of techniques including 4 regression, stochastic Markov models and time series analysis methods such as Autoregressive Integrated Moving Average (ARIMA) models. In general, while emergency demand was universally found to be strongly seasonal and autoregressive it was also extremely variable, with its stochastic nature making accurate forecasts beyond seasonal or monthly means difficult.…”
Section: Introductionmentioning
confidence: 99%